Epidemiological, clinical and spatial characteristics of reported cases of tuberculosis in an endemic area of northeastern of Brazil. - Débora Regina Marques Barbosa; Manoel Guedes de Almeida; Lidiane Mota Martins (Universidade de Santa Cruz do Sul, 2014)
Backgound and Objectives: The tuberculosis (TB) shows itself as a serious health public problem in Brasil and the world, having unequal distribution in population upon particular biological, social, cultural and economic characteristics. Within this context, this paper has in mind describing clinical epidemiological and spatial characteristics of TB cases notified in citizens of Timon, Maranhão, Brasil, in 2011. Methodology: Epidemiological descriptive and retrospective study based in collected data in Information System for Notifiable Diseases and Health Surveillance System of the Municipal Health of the city of Timon. The analysis of cases was through descriptive statistics and risk analysis. Results: 74 new cases of TB were notified in 2011, 55 being new. 62,1% in man, with prevalence of coefficient of 60, 12 cases/100.000hab. and relative risks of 1,74 for male. The major number of cases occurred in individuals between 20 and 39 years old (56,7%), with less than 3 years of study (32,4%) being the clinical pulmonary kind the most common (79,7%). Serologic testing for HIv was positive in 5,4%. The fatality rate for TB was of 2,7% being 25% bigger in patients with TB-HIV infection. The neighborhood of Parque Piauí concentrated the bigger amount of cases (19,9). Conclusion: This work enabled general characteristics of the disease in the city, as much as like it's spatial distribution per neighborhood, to potentiate the actions aimed at combating the disease in the city. KEYWORDS: Tuberculosis. Epidemiology. Distribution.